A Survey on the State of Practice in the Adoption of Schema Matching in Brazilian Companies - Borges, Ricardo H. D.; Ribeiro, Leonardo Andrade; Graciano Neto, Valdemar V. (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2025)
Context: Data integration is a fundamental activity for achieving full interoperability between Information Systems (IS). One of the most critical steps in this process is schema matching, which involves identifying correspondences between schema elements to ensure that equivalent information is correctly associated. Problem: The schema matching activity can be extremely time-consuming, expensive, repetitive, labor-intensive, and error-prone, potentially leading to significant losses. In this context, companies can employ tools to support or partially/fully automate this activity. However, the current state of such practices in Brazil remains unclear. Solution: Understanding the state of practice in Brazil can help guide research and development efforts by revealing how data integration is currently conducted in companies. This provides evidence of practical approaches and informs the structuring of training programs and the development of technologies to support such initiatives. IS Theory: We rely on Socio-technical systems theory, since we consider social and technical aspects as interdependent parts of a complex system. Method: A survey research was carried out. Summarization of Results: Thirty-five data professionals from 12 states and the Federal District participated in the survey. The results show that, despite familiarity with the concept, practical adoption faces challenges such as schema complexity, a lack of tools, and the absence of specific training. Nevertheless, for those who apply the technique, the benefits are clear: (i) more efficient data integration, (ii) error reduction, and (iii) increased agility. Contributions and Impact on the IS Area: The results contribute by providing evidence that can help guide research efforts and technological advancements to support schema matching in Brazil. This aims to enable full interoperability among information systems in the future, addressing Brazil’s Grand Challenges in Information Systems, such as Systems-of-Systems, Smart Cities, and Full Interoperability, which serves as an enabler for the other two.